Experimental Fishing in Hirakud Reservoir , Orissa (1965-67) - SULOCIIANAN, P.; GEORGE, V. C.; NAIDU, R. M. (Fishery Technology, 1968)
The comparative efficiencies of simple gill net, vertical linenet and framed net in exploiting the fishery of Hirakud Reservoirin Orissa were studied. Though comparatively costlier to fabricate,the framed net gave better results than the other two.